Pendidikan Karakter di Era Digital: Tantangan dan Strategi dalam Membentuk Generasi Berakhlak Mulia - Salsa Nurhabibah; Herlini Puspika Sari; Siti Fatimah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The digital era has brought major changes to various aspects of life, including in the world of education. One of the main challenges that has emerged is how to shape the character of the younger generation amidst the flow of information that is so fast, free, and uncontrolled. The negative influence of social media, the decline in direct social interaction, and weak control over digital content consumed by students are serious obstacles in the implementation of character education. This article discusses these challenges while offering strategies that can be implemented by educators, parents, and educational institutions. The strategies outlined include the wise integration of technology in character learning, strengthening the role of the family as the first and foremost educational environment, and the importance of role models and consistency of moral values in everyday life. Through an adaptive, collaborative, and sustainable approach, character education can remain the foundation in forming a generation that is not only intellectually intelligent, but also has integrity, responsibility, and noble character in the digital era.